2019
DOI: 10.1111/jfd.13074
|View full text |Cite
|
Sign up to set email alerts
|

Selection response forStreptococcus agalactiaeresistance in Nile tilapiaOreochromis niloticus

Abstract: The potential of selection to improve resistance to streptococcosis was evaluated in a commercial population of Nile tilapia in Thailand. The base generation (G0) consisted of offspring from 98 sires and 149 dams using a partly nested design. At 60 days post‐hatch, 30 fish from each family were injected intraperitoneally with a Streptococcosis agalactiae solution (1 × 109 CFU/ml) and evaluated for 14 days. Disease resistance was recorded as the number of days from challenge until death (DD) and as a binary (BI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 43 publications
(91 reference statements)
0
14
0
2
Order By: Relevance
“…Myogenesis corresponds to the formation of muscle fibers involved in the differentiation, fusion, and absorption of myogenic precursor cells to form syncytial fibers 61 . Additionally, resistance to infectious diseases is an economically relevant trait and is considered a long-term aim because of the consequences of this trait on fish health and growth 62 . In Nile tilapia there are programs that select for disease resistance 7 , but none of the strains used in this study has been artificially selected for disease resistance.…”
Section: Signatures Of Selectionmentioning
confidence: 99%
“…Myogenesis corresponds to the formation of muscle fibers involved in the differentiation, fusion, and absorption of myogenic precursor cells to form syncytial fibers 61 . Additionally, resistance to infectious diseases is an economically relevant trait and is considered a long-term aim because of the consequences of this trait on fish health and growth 62 . In Nile tilapia there are programs that select for disease resistance 7 , but none of the strains used in this study has been artificially selected for disease resistance.…”
Section: Signatures Of Selectionmentioning
confidence: 99%
“…This validation can be done either in laboratory or in the field conditions. It has been shown via experimental validation that the risk of mortality can decrease up to 54% by selecting for S. agalactiae in Nile tilapia (Suebsong et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The correlation pattern between disease resistance and growth is host-specific and pathogen-specific (Gjedrem 2015). On the other hand, Suebsong et al (2019) reported the same thing selective breeding programs have significant potential to make tilapia more resistant to Streptococcus agalactiae. Heritability estimates for G0 were 0.22 using the Cox model.…”
Section: Discussionmentioning
confidence: 99%